An Analytical Study of the Concept of Time in the Qur'an, Surah Al-Ashr: Ibn Kathir's Tafsir - Cahyani, Dhea; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
The Qur'an, as the holy book of Muslims, not only contains spiritual and moral guidance but also touches on aspects of human life, including the values of time. Surah Al-Ashr is a part of the Qur'an, which specifically discusses the value of time and provides in-depth teaching regarding the importance of valuing time in the journey of human life. In the journey of life, time is a very valuable and significant aspect. In the context of the values of a Muslim's life, the Qur'an, as the main guideline, provides instructions regarding how humans should view and utilize time. One surah that explicitly highlights the value of time is Surah Al-Ashr. This study will analyze the time value in the Qur'an, especially in Surah Al-Ashr, by considering the views in